The Major Histocompatibility Complex B (MHC-B) and QTL Microsatellite Alleles of Favorable Effect on Antibody Response against the Newcastle Disease - Hako Touko, B.A.; Keambou, T.C.; Han, J.M.; Bembide, C.; Cho, C.Y.; Skilton, Robert A.; Djikeng, Appolinaire; Ogugo, M.; Manjeli, Y.; Tebug Tumassang, T.; Zoli, P.A.; Osama, S. (2013)
The molecular typing and the indirect ELISA procedure were used to identify some alleles of favorable effect on the antibody response against the Newcastle disease virus (NDV). The NDV seroprevalence was 100.00% with 10.47% suspect and 89.63% positives. The protective level of ELISA antibody mean titre was 1409.43U/ml and 16.26% of the tested birds were considered tolerant. A total of 10 alleles of which 4 from the MHC-B Marker LEI0258 and 6 alleles from 5 QTL markers associated with resistance/tolerance against the NDV, namely LEI0070 (2 alleles) and only 1 allele for ADL0146, LEI0104, ADL0320 and ADL0304 respectively were shown to have a favorable effect on the antibody titre. The naked neck chicken was associated with high antibody response (1816.27 to 2227.55 U/ml) compare to the others (1409.48 to 1842.54 U/ml) and their phenotypic frequency was relatively higher (23.08) in the selected population compare to the sampled population (10.47) but, no MHC or QTL allele were private to the naked neck. These results suggest an evidence of genetic disease resistance within Cameroon native chicken populations and confirm the implication of the MHC-B in the immune response in general, and against the Newcastle disease virus in particular.